An electrophysiological investigation of orthographic spatial integration in reading. (June 2019) - Snell, Joshua; Meade, Gabriela; Meeter, Martijn; Holcomb, Phillip; Grainger, Jonathan
Abstract: During reading, word recognition speed is influenced by the amount of orthographic overlap with surrounding words. The nature of this phenomenon is not understood: some theories attribute it to low-level visual operations (i.e., parafoveal feature detectors influencing foveal letter detectors), whereas other theories assume that orthographic processing (i.e., letter position coding and word activation) occurs across multiple words in parallel. To arbitrate between these theories, we used electroencephalography to reveal the time course of orthographic spatial integration in a lexical decision task. Foveal target words were flanked on each side by parafoveal words, manipulated across three conditions: repetition flankers (e.g. rock rock rock ), unrelated flankers ( step rock step ) and a no-flanker condition. Linear mixed-effect models were constructed to analyze EEG data on a trial-by-trial basis. Word recognition was worse in the unrelated flanker condition than in the repetition and no-flanker conditions. This behavioral pattern was accompanied by increased negativity in the N250 and N400 windows, associated with the activation of sub-lexical and lexico-semantic representations, respectively. Crucially, the absence of effects prior to 200 ms post-stimulus onset provides evidence against the involvement of low-level visual processes. We conclude that orthographic spatial integration is driven by parallel processing of multiple words, which leads to the activation of a larger set of sub-lexical nodes and more difficult processing at the lexical level when those words are orthographically unrelated. Highlights: Words are recognized faster when they share many letters with surrounding words. EEG measurements suggest that this effect unfolds 200 ms after stimulus onset. The locus of effects contradicts the involvement of low-level visual processing. Instead, the phenomenon appears to be driven by parallel orthographic processing.